Pathogenesis of Theiler's Murine Encephalomyelitis Virus - Yamada, Masahito (Adv Virus Res, 1991)
Theiler's murine encephalomyelitis virus belongs to the family of picornaviridae. Picornaviruses are small ( “pico”), phylogenetically related RNA viruses. Based on different biochemical and biophysical characteristics picornaviruses are subdivided into four groups: enteroaphthovirus (foot-and-mouth disease virus), cardiovirus [encephalomyocarditis virus (EMCV), Mengo virus], and rhinovirus (human rhinovirus). Theiler's murine encephalomyelitis virus was originally classified among the picornaviridae as an enterovirus because of its biological similarities with poliovirus. Further comparison of the complete genome of TMEV BeAn 8386 strain identifies remarkable similarities at the level of nucleotides and predicted amino acids between BeAn and the cardioviruses EMCV and Mengo virus. Theiler's murine encephalomyelitis virus is a single-stranded nonenveloped RNA virus. The viral RNA is of positive sense, having the same polarity as mRNA. Viral mRNA lacks the cap structure found at the 5’ end of almost all eukaryotic mRNAs.